Persepsi Masyarakat Terhadap Pemanfaatan Obat Tradisional Untuk Antidiabetes Di Kecamatan Kuta Cot Glie Kabupaten Aceh Besar - Burdah, Burdah; Silviana, Ernita; sari, amelia; Mauyah, Nizan; irwani, maria (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2024)
Diabetes mellitus (DM) is a disease characterized by an increase in blood glucose levels. According to the International Diabetes Federation (IDF), Indonesia ranks 7th with 8.5 million diabetes mellitus sufferers. The use of plants as traditional medicine for various diseases has been widely used, traditional medicine from natural ingredients has become an alternative treatment, one of which is diabetes. This research aims to determine the public's perception of the use of traditional medicines for anti-diabetes in Kuta Cot Glie District, Aceh Besar Regency. This research is descriptive quantitative with a cross sectional approach. The sampling technique used is a purposive sampling technique, namely a sampling technique with certain considerations. The results of data analysis showed that the public's perception of the use of traditional medicines for anti-diabetes was mostly in the good category, 26 people (86.7%) and the most people used traditional medicines for anti-diabetes, namely 14 people (46.7%). So it can be concluded that the public's perception of the use of traditional medicine for anti-diabetes in Kuta Cot Glie District is in the good category.